PENGARUH KESADARAN WAJIB PAJAK, PELAYANAN FISKUS, PENYULUHAN WAJIB PAJAK DAN SANKSI PAJAK TERHADAP TINGKAT KEPATUHAN FORMAL WAJIB PAJAK ORANG PRIBADI PADA KANTOR PELAYANAN PAJAK PRATAMA BATAM - Mortigor Afrizal Purba (LPPM Universitas Putera Batam, 2019)
This study examines the level of compliance of individual taxpayers in KPP Pratama Batam by using several independent variables such as awareness of the taxpayer, the service tax authorities, tax information and tax penalties. The purpose of this study was to analyze the influence of awareness of the taxpayer, the service tax authorities and tax sanctions against an individual taxpayer. The population of this study is individual taxpayers in Batam. Based on data from the KPP Pratama Batam, until the end of 2016 there were 90.768. Not all population have been used in this study to the time and cost efficiency. Therefore, carried out the sampling. Sampling was done by simple random sampling method. The number of sample is 200 people. Primary data collection method used is a survey method using questionnaires media. Data analysis techniques used in this study is the technique of multiple regression analysis. Based on the results of the analysis undertaken concluded that awareness of the taxpayer, the service tax authorities, tax information and tax sanctions have a positive and significant impact on taxpayer compliance.